Preparation and characterization of ancient recipe of organic Lime Putty-Evaluation for its suitability in restoration of Padmanabhapuram Palace, India - M. Shivakumar (Nature Portfolio, 2021)
Abstract The study aims at preparation and characterization of six organic lime putty (hydraulic Lime + fermented plant extract) using regionally available plants namely Terminalia Chebula (kadukkai), Rosa Sinensis (hibiscus), Palm jaggery (refined sugar), Xanthorrhoeaceae (aloe vera), and Indigofera Tinctoria (neelamari) as per the methods given in the ancient palm leaf of Padmanabhapuram Palace, India. Advanced analytical techniques like Gas chromatography-mass spectroscopy (GC–MS), UV-Spectrophotometer and carbon dioxide quantification were used to study the fermented plant extracts and Fourier transform-infrared spectroscopy (FT-IR), X-ray Diffraction (XRD), Field emission-scanning electron microscopy (FESEM) to study hydrated phases and microstructure of organic lime putty. GC–MS recorded the phytochemical compounds like fatty acids, traces of proteins, polysaccharides and carbohydrates. Fermented kadukkai and neelamari extracts reported as fatty acid, palm jaggery as carbohydrate, hibiscus as polysaccharide and aloevera rich in all the biomolecules. The detection limit of Quantification:0.013 and limit of detection:0.067 for polysaccharides, 0.026 and 0.088 for unsaturated fatty acids was reported through a U.V spectrophotometer for all the herbs. Aloevera and neelamari fermented extracts recorded the CO2 release around 96,000 and 90,000 ppm on 4th day of fermentation, whereas for other herbs it ranged below the recorded readings. Supply of CO2 has initiated the internal carbonation of the lime putty and precipitation of calcite in three different forms aragonite, calcite and vaterite minerals. The addition of organics resulted in high-intensity portlandite peaks and calcium carbonate polymorphs as reported in XRD graphs in agreement with FT-IR analysis. FESEM morphology validated the early formation of carbonate polymorphs, and EDX. has shown that kadukkai lime putty, jaggery lime putty and reference lime putty. mixes have calcium around 35–45%. From the overall results, 3% addition of eco-friendly biopolymers has altered the properties like setting time, water repellency and higher carbonation rate, which is the main reason behind longevity of the structure.